2019
DOI: 10.1002/dys.1628
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' knowledge about language constructs related to literacy skills and student achievement in low socio‐economic status schools

Abstract: Teachers' knowledge is a critical component to students learning to read proficiently. The present research sought to determine the literacy knowledge of 150 urban, elementary school teachers from 11 low socio-economic schools in one of nation's largest cities. Teachers' ability to understand concepts relating to phonological awareness, phonemic awareness, alphabetic principle/phonics, and morphology as well as their knowledge about teaching these fundamental skills were assessed through a standardized measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
30
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 37 publications
6
30
0
2
Order By: Relevance
“…This discrepancy in beliefs and knowledge might obscure teachers' aware ness of the need to increase their knowledge. Moreover, research has demonstrated that teachers may not deepen their knowledge of concepts related to reading instruc tion through teaching experience alone (McCutchen et al, 2002;Pittman et al, 2020;Washburn et al, 2011b).…”
Section: Teacher Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy in beliefs and knowledge might obscure teachers' aware ness of the need to increase their knowledge. Moreover, research has demonstrated that teachers may not deepen their knowledge of concepts related to reading instruc tion through teaching experience alone (McCutchen et al, 2002;Pittman et al, 2020;Washburn et al, 2011b).…”
Section: Teacher Preparationmentioning
confidence: 99%
“…Research has consistently demonstrated that for early elementary students and older struggling readers, explicit instruction of foundational literacy skills provides stu dents from a wide variety of backgrounds with the greatest opportunity to learn to read proficiently (e.g., Blachman, Tangel, Ball, Black, & McGraw, 1999;D'Angiulli, Siegel, & Maggi, 2004;Torgesen et al, 2001). However, teachers, in general, have an insufficient understanding of foundational literacy skills necessary for providing effective reading instruction based on the science of reading (e.g., Brady & Moats, 1997;Moats & Foorman, 2003;Pittman, Zhang, Binks Cantrell, Hudson, & Joshi, 2020;Spear Swerling & Cheesman, 2012;Washburn, Binks Cantrell, Joshi, Martin Chang, & Arrow, 2016). Literacy researchers have pointed to teacher preparation programs as the reason for knowl edge gaps among educators (Binks Cantrell, Washburn, Joshi, & Hougen, 2012;Greenberg, Walsh, & McKee, 2015;ILA, 2020;Joshi et al, 2009;Moats, 2014Moats, , 2020, which has stimulated interest in rais ing teachers' literacy knowledge (ILA, 2018;Inter national Dyslexia Association, 2018).…”
mentioning
confidence: 99%
“…Researchers have critiqued the lack of knowledge base that some practicing K-12 teachers hold to teach beginning and/or struggling readers (Binks-Cantrell, Washburn, & Joshi, 2020;Joshi et al, 2009). Background knowledge about phonics varies for teachers and teacher candidates regarding the more technical aspects of literacy learning in that area (Pittman, Zhang, Binks-Cantrell, Hudson, & Joshi, 2020). Research also has suggested that some teachers have gaps in their background knowledge about phonics (Cunningham, Perry, Stanovich, & Stanovich, 2004;Joshi et al, 2009).…”
Section: Addressing Gaps In Teacher Knowledgementioning
confidence: 99%
“…The researchers were particularly interested in knowing whether service learning benefitted teacher candidates by increasing their literacy knowledge, skills, and efficacy. Research has consistently shown that many in-service teachers are not prepared to teach literacy (Pittman, Zhang, Binks-Cantrell, Hudson, & Joshi, 2019;Joshi et. al, 2009;Moats, 1999); therefore, the researchers were interested in determining if service learning would increase teacher candidates in the aforementioned areas through a servicelearning experience.…”
mentioning
confidence: 99%